EMPLOYING SCAMPER TO DEVELOP CREATIVE THINKING IN TEACHING ARABIC AS A SECOND LANGUAGE - Elwakeel, Mahmoud Ahmed; Ramadan, Hany Ismail; Alabri, Khalid Hilal (Veredas do Direito, 2026)
Though the greater number of Arabic language teaching programs for non-native speakers, such programs still rely on traditional methods neglecting higher-order thinking skills and linguistic creativity. Hence, this study sought to investigate the better employment of SCAMPER strategy for developing creative thinking in Arabic as a second language programs. Basically, the SCAMPER strategy, the seven-technique strategy, is a novel educational strategy that focuses on developing creative thinking, motivating learners to generate ideas and address problems creatively. Methodologically, the study used the descriptive approach to achieve its objective. Ultimately, the study concluded that the SCAMPER strategy proved significance in developing creative thinking in Arabic language programs for non-native speakers, given its suitability for cultural and linguistic characteristics. Additionally, the study emphasized that integrating SCAMPER into the design of educational units is an effective tool for developing the content of Arabic language programs for non-native speakers. It also presented a set of practical and diverse applications for employing the seven SCAMPER strategies in Arabic language programs for non-native speakers across all language skills. Finally, the study recommended integrating the SCAMPER strategy into Arabic language curricula for non-native speakers, training teachers on its use, and designing educational activities in light of the strategy.